2018
DOI: 10.1039/c8cc00016f
|View full text |Cite
|
Sign up to set email alerts
|

Advanced emulsions via noncovalent interaction-mediated interfacial self-assembly

Abstract: We demonstrate that the traditional emulsification theory can be enriched by a self-assembly approach, in which hydrophilic copolymers with one block exhibiting noncovalent forces with the oil phase self-assemble at the oil-water interface, thereby reducing interfacial tension and forming emulsions. This approach was established using affinity diblock copolymers that can interact with oil molecules through electrostatic interactions or hydrogen-bonding. Nanoemulsions with excellent stability were successfully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…These results suggested that the supra-amphiphilic host–guest engineering polymers exhibited good interfacial adsorption kinetics behaviors in the presence of polymeric alginate chains . There have been several reports on the fabrication of colloidal nanoparticles by introducing a dynamic intermolecular recognition engineering interfacial self-assembly strategy, involving electrostatic interactions and π–π stacking . Yet, the colloidal assemblies were generally rigid nanoparticles, , considering that the soft assemblies exhibit relatively better interfacially structural controllability as compared with rigid particles. , Therefore, the supra-amphiphilic polymers seem to be an excellent alternative to tailor-matched amphiphilicity for regulating interfacial self-assembled behaviors.…”
Section: Resultsmentioning
confidence: 96%
“…These results suggested that the supra-amphiphilic host–guest engineering polymers exhibited good interfacial adsorption kinetics behaviors in the presence of polymeric alginate chains . There have been several reports on the fabrication of colloidal nanoparticles by introducing a dynamic intermolecular recognition engineering interfacial self-assembly strategy, involving electrostatic interactions and π–π stacking . Yet, the colloidal assemblies were generally rigid nanoparticles, , considering that the soft assemblies exhibit relatively better interfacially structural controllability as compared with rigid particles. , Therefore, the supra-amphiphilic polymers seem to be an excellent alternative to tailor-matched amphiphilicity for regulating interfacial self-assembled behaviors.…”
Section: Resultsmentioning
confidence: 96%
“… 25 The former produces particles of limited size range and may require an additional step for polymer crosslinking, while the latter is applicable only to conductive polymers. In contrast, the phase separation method, 26 e.g. emulsion solvent evaporation, is generally recognized as the most feasible method for scalable production of JP owing to its economical set-up and relatively simple process.…”
Section: Introductionmentioning
confidence: 99%